Gene-Protective Narratives: The Arabian Nights Reconsidered - Pagan, University of Malaya, Malaysia, Nicholas O. (Asiatic: IIUM Journal of English Language and Literature, 2016)
While acknowledging the importance of Mark Turnerâ€™s claim that Shahrazad, the character from The Arabian Nights, epitomises the â€œliterary mind,â€ this paper points to possible shortcomings in his argument. Through careful consideration of Shahrazadâ€™s function in the narratives within narratives that make up The Arabian Nights, the paper plays down the literary dimensions of her storytelling ability, drawing attention instead to the ways in which she invariably uses language as an instrument designed to achieve a specific end. By incorporating ideas from thinkers outside of the humanities -- especially Daniel C. Dennett and Richard Dawkins â€“ the paper offers a new reading of The Arabian Nights, which incorporates the contention that Shahrazad is both a user of language and is used by language â€“ a spinner of webs of narrative who is also caught up in these webs. Distinguishing carefully between genes and the bodies that contain them, the paper proposes that a fundamental aspect of Shahrazadâ€™s identity is that she is a vehicle for the spreading of genes. Finally, generalising from the stories contained in The Arabian Nights, the paper concludes that other literary narratives may also turn out to be more fundamentally gene-protective than they are â€œliterary.â€